Parasitic infections amongst migrant workers in Malaysia / Norhidayu Sahimin - Norhidayu, Sahimin (2017)
Sociodemographic background of 610 migrant workers employed in Malaysia was collected via questionnaire to determine their parasitic health status. Six nationalities were recruited with most workers from Indonesia (49.5%), followed by Bangladesh (19.2%), Nepal (16.4%), India (10.5%), Myanmar (4.3%) and Vietnam (0.2%) and employed in five working sectors namely; domestic service (24.3%), construction (22.8%), food service (21.0%), plantation (16.7%) and manufacturing (15.2%). A total of 388 individuals provided faecal samples for parasitic screening via microscopy. Four nematode species (Ascaris lumbricoides, Trichuris trichiura Enterobius vermicularis, and hookworms), one cestode (Hymenolepis nana) and three protozoan species (Entamoeba histolytica/dispar, Giardia spp. and Cryptosporidium spp.) were recovered. High prevalence of infections with Ascaris lumbricoides (43.3%) was recorded followed by hookworms (13.1%) and E. histolytica/dispar (11.6%) with infections significantly influenced by nationality, years of residence in Malaysia, employment sector and education level. Toxoplasma gondii infections were screened serologically from 484 workers with more than half of the workers were seropositive (57.4%) with 52.9% seropositive for anti-Toxoplasma IgG only, 0.8% seropositive for anti-Toxoplasma IgM only and 3.7% seropositive with both IgG and IgM antibodies. Samples positive for both IgG and IgM antibodies were further tested for IgG avidity showed high avidity suggesting latent infection in 18 workers. Four significant factors recorded namely; age, nationality, employment sector and length of residence in Malaysia. Three diagnostic methods were tested and compared to detect Strongyloides stercoralis infections in 306 migrant workers with 37.6% were seropositive. Subsequent confirmation using a nested PCR showed successful amplification from three males (2.6%) with target amplicon of approximately 680bp. For the three methods, nested PCR was the most sensitivity method in the detection for strongyloidiasis and should be applied in future studies. PCR method was also applied to determine the species level for four parasite‘s genus recovered in the population. Internal transcribed spacer 2 and 28S ribosomal RNA region of N. americanus and Ancylostoma spp. was successfully amplified and resulted in A. duodenale reported for the first time in Malaysia. Nested PCR targeting 16S-like ribosomal RNA gene successfully recovered E. dispar as the most dominant infection among workers. Despite the low presence of E. histolytica in the population, it still carries a public health risk. Amplification of the triosephosphate isomerase (TPI) gene from G. duodenalis isolates successfully obtained the presence of assemblage B and sub-assemblage AII suggesting the mode of transmission was human-to-human. Based on the SSU rRNA gene, the C. parvum amplicons were successfully detected in 9 human isolates.